Kinetika Reaksi Epoksidasi In-Situ Minyak Biji Kapuk = Reaction Kinetics Of In-Situ Epdxidation Of Kapok Oil - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The reaction kinetics of the epoxidation of kapok oil by peroxyacetic acid generated in situ were studied. About 100 mL of oil, a certain amount of acetic acid, and sulfuric acid were mixed together and heated to the desired temperature. A certain amount of hydrogen peroxide was added at once to the heated oil. Samples were taken out of the reaction vessel periodically and immediately poured into 50 mL erlenmeyer flasks containing about 30 mL of NaHCO3 0,1 M at room temperature. The oil-water mixture was stirred with a teflon spinbar for at least one min to allow extraction of the adds from the oil into the water. The oil-water mixture was then separated by centrifugation at 3500 rpm for 2 min in a centrifuge tube. A small quantity of the oil phase was removed from the top with a pipette for analysis. Agitation speed, temperature, and equivalent ratio of acetic acid to hydrogen peroxide were studied in this investigation. Based on the Reynolds index and the increase of reaction rate constant caused by a 10Â°C increase of temperature, it was obvious that the reaction rate was controlled by chemical reaction. Within the range of variables studied, temperature affected the reaction rate constant, kir exponentially, while equivalent ratio of acetic acid to hydrogen peroxide and speed of agitation, showed logarithmic relation with k1.